Exciting Coil Optimization Criteria for Eddy Current Detection of Small Cracks under Fastener Head, ISSN 1582-4594 - Bouchala Tarek; Benhadda Nabil; Bachir Abdelhadi (Journal of Electrical Engineering, 2016)
The aim of this paper consists of presenting optimization criteria of coil dimensions and the exciting field frequency in order to improving eddy current probe sensitivity for small and deep cracks under fasteners. To accomplish this task, we have studied the influence of coil inner radius, coil height and exciting frequency on probe sensitivity. Then, an algorithmic searching technique is applied to determine the optimal values of the previous parameters. Hence, the obtained results have revealed that the optimum inner radius corresponds exactly to the fastener head outer radius. Furthermore, it has been noticed that as well as the coil height is reduced while keeping the same number of turns, the probes sensitivity increases. Indeed, the use of stacking flat micro-coils is well adapted. In addition, the calculation of the optimum values of the frequency demonstrate that this parameter depend relatively on the defect position, its radial and vertical depth.